Adapting the built environment for climate change : design principles for climate emergencies - Pacheco-Torgal, Fernando; Goran-Granqvist, Claes (Woodhead Publishing, an imprint of Elsevier, 2023)
Adapting the Built Environment for Climate Change: Design Principles for Climate Emergencies analyzes several scenarios and proposes various adaptation strategies for climate emergencies (heat waves, wildfires, floods, and storms). Divided into three themes, the book offers an organized vision of a complex and multi-factor challenge. It covers climatic resilience and building refurbishment, implications for service life prediction and maintainability, and climate adaptation in the maintenance and management of buildings. Sections cover infrastructure materials, climate emergency adaptation and building adaptation to heat waves, wildfires, floods and storms. The book will be an essential reference resource for civil and structural engineers, architects, planners, designers and other professionals who have an interest in the adaptation of the built environment against climate change.
Keywords: Buildings -- Repair and reconstruction.; Climate change mitigation.; elektronické knihy; electronic books